Organic produce And now for that certificate - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Access to the growing organic produce markets in the West is subject to strict rules of certification. In Europe, produce has to conform with various certification schemes, rooted in the rules established by the International Federation of...